Afrofuturism : the world of black sci-fi and fantasy culture - Womack, Ytasha (Lawrence Hill Books, an imprint of Chicago Review Press, 2013)
Comprising elements of the avant-garde, science fiction, cutting-edge hip-hop, black comix, and graphic novels, Afrofuturism spans both underground and mainstream pop culture. With a twofold aim to entertain and enlighten, Afrofuturists strive to break down racial, ethnic, and all social limitations to empower and free individuals to be themselves. This book introduces readers to the burgeoning artists creating Afrofuturist works, the history of innovators in the past, and the wide range of subjects they explore. From the sci-fi literature of Samuel Delany, Octavia Butler, and NK Jemisin to the musical cosmos of Sun Ra, George Clinton, and the Black Eyed Peas' will.i.am, to the visual and multimedia artists inspired by African Dogon myths and Egyptian deities, topics range from the alien experience of blacks in America to the wake up cry that peppers sci-fi literature, sermons, and activism. Interviews with rappers, composers, musicians, singers, authors, comic illustrators, painters, and DJs, as well as Afrofuturist professors, provide a firsthand look at this fascinating movement.